Student’s perceptions towards the teaching and learning of jawi (Arabic letter) under j-QAF programme: a case study at selected government primary schools in the District of Hulu Selangor. - Mamat , Arifin; Kamis, Rohani; Abd Rashid, Adnan (2012)
In Malaysian Educational System, Islamic Education is one of the core subject offered in the primary schools for Muslim students. Anyhow, studies have shown that they are weak in Jawi skills (writing and reading Arabic letter). Therefore, the Ministry of Education, Malaysia has designed special programme called jQAF to enhance student’s ability in Jawi, Qur’an, Arabic and Fard ‘Ain. Thus, this study attempts to investigate the teaching strategies applied by Islamic Education teachers in teaching Jawi. The researcher has conducted a case study using self-constructed questionnaires. The respondents comprised of 255 year six students from the selected Government Primary Schools in the district of Hulu Selangor. A descriptive analysis was employed to provide meanings to the data. This simple descriptive statistical analysis includes percentages, frequencies and means. The findings revealed that there are several methods applied by teachers in teaching Jawi. It was also found that students have positive perceptions towards Jawi subject. Generally, this study provides useful insights that can be benefited by J-QAF teachers and the Ministry of Education.